Science on the Oregon Trail - Enz, Tammy (Science of history (Capstone Press), 2022)
"You may have heard of the Oregon Trail. In the 1840s, more than 5,000 people traveled the Oregon Trail, hoping for a better life. But did you know that science played a big role in this epic journey? Learn how covered wagons were engineered. Find out how food was preserved and diseases were treated along the trail. And discover how modern technology is helping us learn even more about this time in history"--